2015
DOI: 10.1038/bmt.2015.119
|View full text |Cite
|
Sign up to set email alerts
|

Integration of humoral and cellular HLA-specific immune responses in cord blood allograft rejection

Abstract: In allo-stem cell transplantation (SCT), it is unclear whether donor-specific anti-HLA Abs (DSAs) can actually mediate graft rejection or if they are simply surrogate markers for the cellular immunity that causes graft rejection. Here, we first analyzed a case of cord blood allograft rejection in which DSA and cytotoxic T lymphocyte (CTL) specific for donor HLA-B*54:01 were detected at the time of graft rejection. Both the DSA and CTL inhibited colony formation by unrelated bone marrow mononuclear cells sharin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…TCR-b deep sequencing was performed as described previously [14,15], with some modifications, using an Illumina MiSeq sequencer (Illumina, San Diego, CA) instead of a Roche 454 sequencer (Roche, Basel, Switzerland). In brief, cDNA was generated from total RNA using a SMARTer RACE 5 0 /3 0 kit (Takara Bio, Kusatsu, Japan).…”
Section: Tcr-b Deep Sequencingmentioning
confidence: 99%
“…TCR-b deep sequencing was performed as described previously [14,15], with some modifications, using an Illumina MiSeq sequencer (Illumina, San Diego, CA) instead of a Roche 454 sequencer (Roche, Basel, Switzerland). In brief, cDNA was generated from total RNA using a SMARTer RACE 5 0 /3 0 kit (Takara Bio, Kusatsu, Japan).…”
Section: Tcr-b Deep Sequencingmentioning
confidence: 99%
“…In unrelated donor HCT, DSAs cause graft failure and the presence of antibodies against HLA-DP was quite prominent, being observed in 60% of antibody-positive failures (25). In a study on data from the database of Japan Society for Hematopoietic Cell Transplantation (JSHCT), researchers have demonstrated that DSAs were associated with an increased risk of graft failure after CBT (34). In our study, we found that the presence of anti-HLA Abs does not have an impact on platelet engraftment, although the mechanisms behind this need further studies (35).…”
Section: Discussionmentioning
confidence: 99%
“…In unrelated donor HCT, DSAs cause graft failure and the presence of antibodies against HLA‐DP was quite prominent, being observed in 60% of antibody‐positive failures 32 . In a study on data from the database of Japan Society for Hematopoietic Cell Transplantation (JSHCT), researchers have demonstrated that DSAs were associated with an increased risk of graft failure after CBT 40 . In our study, we found that the presence of anti‐HLA Abs does not have an impact on platelet engraftment, although the mechanisms behind this need further studies 41 …”
Section: Discussionmentioning
confidence: 99%